Predictive factors for severe placental damage in pregnant women with SARS-CoV-2 infection - Damman, Elise; Trecourt, Alexis; de la Fournière, Benoit; Lebreton, Frédérique; Gaillot-Durand, Lucie; Fichez, Axel; Chauvy, Lauriane; Thonnon, Cyrielle; Destras, Gregory; Devouassoux-Shisheboran, Mojgan; Allias, Fabienne (Placenta (Eastbourne), 2023)
SARS-Cov-2 infection during pregnancy can lead to severe placental lesions characterized by massive perivillous fibrin deposition, histiocytic intervillositis and trophoblast necrosis. Diffuse placental damage of this kind is rare, but can sometimes lead to obstetric complications, such as intrauterine fetal death (IUFD). The objectives of this study were to identify possible predictors of severe placental lesions. We retrospectively studied 96 placentas from SARS-Cov-2 positive pregnant women who gave birth between March 2020 and March 2022. Cases with and without severe placental lesions were compared in terms of clinical and laboratory findings. Twelve of the 96 patients had severe placental lesions. There was no significant association with diabetes, obesity or severe clinical maternal disease. In contrast, presence of severe placental lesions was significantly associated with neonatal intensive care, cesarean section, prematurity, IUFD, intrauterine growth restriction (IUGR), gestational age, maternal hypofibrinogenemia and thrombocytopenia. No cases of severe placental lesions were observed in vaccinated patients or in those with the Omicron variant. In these patients, severe placental lesions due to SARS-Cov-2 were significantly associated with the presence of coagulation abnormalities (hypofibrinogenemia and thrombocytopenia), IUGR and gestational age. These results support laboratory and ultrasound monitoring of these parameters in pregnant women with SARS-Cov-2 infection, especially during the second trimester, to predict potential negative fetal outcomes. •None of the patients with severe placental damage had severe COVID-19.•Severe placental damage was significantly associated with maternal hypofibrinogenemia.•Severe placental damage was significantly associated with maternal thrombocytopenia.•Severe placental damage was associated with poor fetal outcomes.•No cases of severe placental damage in vaccinated or Omicron-infected patients